Assessment Oxidative Stress and Antioxidants in Hypothyroidism Patients Before and After Treatment - Nuha Ali Hadi Ali_Samarrai; Rana Raad Zanzal; Mays Subhi Wasmi (Indonesian Journal Publisher, 2025)
Thyroid hormones influence the majority of bodily functions by directly impacting various physiological processes and the operation of numerous tissues. They are essential for the operation of other hormones. Aim of the study : Assessment level of glutathione (GSH), glutathione peroxidase (GSH-PX), and malondialdehyde (MDA), ,Thyroxine (T4) and triiodothyronine (T3),and lipid profile in hypothyroidism women before and after treatment with levothyroxine. Materials and methods: 60 patients (before and after taking Levothyroxine treatment) and 30 control group were selected for the study. The study sample was selected from (15-54) years for the period from the end of September 2024 to the beginning of March 2025. The peak age of women with hypothyroidism was between (35-54) years, and its percentage reached 40%. Samples were taken from people who visit specialists in outpatient clinics and health centers in Samarra city. Result: The serum levels of GSH, GSH-PX, and MDA in hypothyroid patients before and after treatment were significantly distinct from those in the control group (p < 0.001). The lipid profiles, including total cholesterol, triglycerides, low-density lipoprotein (LDL) cholesterol, and high-density lipoprotein (HDL) cholesterol, in the serum of hypothyroid patients exhibited significant differences from those of the control group before and after treatment (p = 0.01). Thyroid hormone levels (TSH, T3, and T4) exhibited a substantial rise (p < 0.01) in the serum of hypothyroid patients pre- and post-treatment in comparison to the control group. Conclusion: The current study concluded increase MDA in patient with hypothyroidism before treatment, while decrease after treatment. In contrast decrease both GSH, GSH-PX, and HDL in in patient with hypothyroidism before treatment, while increase after treatment